Metal complexes of dual-pendant sulfonate bis(indolenine)squaraines. (July 2015) - Lynch, Daniel E.; Cox, Martin
Abstract: Eight metal complexes of dual-pendant sulfonate bis(indolenine)squaraines (four d -transition metals and four f -transition metals) have been prepared and examined as fluorescent probes for solution protein determination. Of the eight, the cobalt-squaraine complex exhibited the highest fluorescence response in the presence of protein (in aqueous solution) and the partial determination of its crystal structure meant that it could be examined further and compared against the previously determined bis-piperidinium and bis-morpholinium squaraine species. Comparative examination of these three variants in water, 10 mM phosphate buffer (pH = 7.0), and 10 mM Tris/HCl buffer (pH = 7.0) led to the conclusion that the use of Tris/HCl buffer resulted in less reduction of fluorescence intensity (over that of water alone) than the more widely used phosphate buffer. Graphical abstract: Highlights: Synthesis of eight metal – dual-sulfonate bis(indolenine)squaraines. Solution examination of fluorescence verses protein concentration performance. Cobalt(II) – squaraine complex exhibits best fluorescence in protein solutions. Fluorescence performance in protein – buffer solution examined. Partial X-ray crystal structures of iron(II) and cobalt(II) – squaraines reported.